2012
DOI: 10.3389/fendo.2012.00074
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Deiodinases and Cancer

Abstract: Deiodinases constitute a group of thioredoxin fold-containing selenoenzymes that play an important function in thyroid hormone homeostasis and control of thyroid hormone action. There are three known deiodinases: D1 and D2 activate the pro-hormone thyroxine (T4) to T3, the most active form of thyroid hormone, while D3 inactivates thyroid hormone and terminates T3 action. A number of studies indicate that deiodinase expression is altered in several types of cancers, suggesting that (i) they may represent a usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 92 publications
1
25
0
1
Order By: Relevance
“…Below we focus on the role played by D2 in the T4-mediated TRH–TSH feedback mechanism, adaptive thermogenesis and myogenesis and muscle regeneration. The reader is referred to other publications for a more comprehensive analysis of the role played by D2 in different biological systems [10,45,6571]. …”
Section: Physiological Roles Played By D2-mediated Thyroid Hormonementioning
confidence: 99%
“…Below we focus on the role played by D2 in the T4-mediated TRH–TSH feedback mechanism, adaptive thermogenesis and myogenesis and muscle regeneration. The reader is referred to other publications for a more comprehensive analysis of the role played by D2 in different biological systems [10,45,6571]. …”
Section: Physiological Roles Played By D2-mediated Thyroid Hormonementioning
confidence: 99%
“…Iodothyronine deiodinase 3 inactivates T3 and terminates its effects. Iodothyronine deiodinase 2 is expressed in multiple tissues, whereas DIO1 expression is virtually restricted to the liver and kidney . Iodothyronine deiodinase 2 has a ~500‐fold higher affinity for T4 than DIO1 .…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates altered expression of DIOs in several types of cancers and many cancer cell lines, including those from CRC highly express DIO3 . An in vitro study showed that inhibition of Wnt signaling, the key initial step for CRC development, reduced DIO3 levels and induced DIO2 levels in Caco‐2 cells .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, D2 is increased in FTC, in anaplastic thyroid cancer (ATC), and in medullary thyroid cancer (MTC), whereas in PTC, glioblastomas and astrocytomas is diminished. 21 Meanwhile, in ATC, which is quite aggressive, alterations have been identified in FOXM1, which codes for the protein Forkhead Box M1, that be-longs to a family of transcription factors involved in the control of cell proliferation, chromosomal stability, and angiogenesis and is highly increased in non-differentiated thyroid cancer. Moreover, high levels of FOXM1 have been linked to a loss of p53 function and uncontrolled activation of the phosphatidylinositol-3 kinase/AKT/FOXO3a pathway.…”
Section: Thyroid Cancermentioning
confidence: 99%